Analisis Kinerja Keuangan Pemerintah Daerah Provinsi Jawa Barat pada Tahun Anggaran 2020-2023 - Chandra, Rifana Nindya; Hidayati, Ani; Wahyuningroem, Rini (INVESTASI : Inovasi Jurnal Ekonomi dan Akuntansi, 2025)
This study aims to analyze the financial performance of the West Java provincial government through the 2020-2023 Budget Realization Report based on the Regional Financial Independence Ratio, the Regional Original Revenue Effectiveness Ratio, and the Fiscal Decentralization Ratio. This research method uses quantitative descriptive data and secondary data sources obtained from the 2020-2023 West Java Provincial Budget Realization Report (APBD), published on the official website at https://djpk.kemenkeu.go.id/. The analysis technique used is quantitative descriptive, using calculations based on the financial data. The analysis results indicate that the Financial Performance of the West Java Provincial Government for 2020-2023, as seen from (1) the Regional Financial Independence Ratio, showed a participatory relationship pattern with a fairly high level of information. (2) the Regional Tax Effectiveness Ratio, indicating that West Java Province was categorized as quite effective in 2020-2023. (3) Fiscal Decentralization Ratio: West Java Province achieved a relatively high level of performance in 2020-2023. This indicates that West Java Province's ability to increase its own-source revenue is quite good, reflecting the excellent performance of the West Java Provincial Government.